Pharmacodynamics and pharmacokinetics of phenylbutazone in calves - A.K., Arifah; Lees, P. (Blackwell Science, 2002)
Phenylbutazone (PBZ) was administered to six calves intravenously (i.v.) and orally at a dose rate of 4.4 mg/kg in a three-period cross-over study incorporating a placebo treatment to establish its pharmacokinetic and pharmacodynamic properties. Extravascular distribution was determined by measuring penetration into tissue chamber fluid in the absence of stimulation (transudate) and after stimulation of chamber tissue with the mild irritant carrageenan (exudate). PBZ pharmacokinetics after i.v. dosage was characterized by slow clearance (1.29 mL/kg/h), long-terminal half-life (53.4 h), low distribution volume (0.09 L/kg) and low concentrations in plasma of the metabolite oxyphenbutazone (OPBZ), confirming previously published data for adult cattle. After oral dosage bioavailability (F) was 66%. Passage into exudate was slow and limited, and penetration into transudate was even slower and more limited; area under curve values for plasma, exudate and transudate after i.v. dosage were 3604, 1117 and 766 μg h/mL and corresponding values after oral dosage were 2435, 647 and 486 μg h/mL. These concentrations were approximately 15-20 (plasma) and nine (exudate) times greater than those previously reported in horses (receiving the same dose rate of PBZ). In the horse, the lower concentrations had produced marked inhibition of eicosanoid synthesis and suppressed the inflammatory response. The higher concentrations in calves were insufficient to inhibit significantly exudate prostaglandin E2 (PGE2), leukotriene B4 (LTB4) and β-glucuronidase concentrations and exudate leucocyte numbers, serum thromboxane B2 (TxB2), and bradykinin-induced skin swelling. These differences from the horse might be the result of: (a) the presence in equine biological fluids of higher concentrations than in calves of the active PBZ metabolite, OPBZ; (b) a greater degree of binding of PBZ to plasma protein in calves; (c) species differences in the sensitivity to PBZ of the cyclo-oxygenase (COX) isoenzymes, COX-1 and COX-2 or; (d) a combination of these factors. To achieve clinical efficacy with single doses of PBZ in calves, higher dosages than 4.4 mg /kg will be probably required.